The effect of concurrent resistance and endurance training on physiological and performance parameters of well trained endurance cyclists - Levin, G. (Edith Cowan University, 2007)
To investigate the effect of concurrent resistance and cycle training on the physiological and performance characteristics of well trained cyclists. Secondly, this study aimed to investigate the reliability of a new cycling time-trial test that incorporated repeated high-intensity sprint segments, both prior to and after a training intervention, with well trained cyclists. Methods: Fourteen well trained cyclists completed a series of physiological and performance tests prior to and following a training intervention period. Following the pre tests, subjects were allocated into two groups; a resistance training group (RT; n = 7) and a control group (C; n = 7). The RT group completed an undulating periodised resistance training program (3/week) for a period of 6 weeks. Testing consisted of a VO2max test, a 30km time trial with 3 intermittent sprinting periods of 250m and 1km each, 1-RM testing for strength and a repeat jump test to measure power off the bike. After a familiarisation trial, all tests were repeated to allow for assessment of reliability both pre and post training. Results: Upon completion of the training intervention, the change in time trial and sprinting performance did not differ between the RT and C group. There was however a trend suggesting that sprinting performance may have been negatively influenced with RT (ES 0.5 - 0.9). Nevertheless, the RT group increased strength to a greater degree than the C group (p < .05) as well as improving their ability to resist fatigued during a repeated jump test (ES = 0.5). Lastly, all tests performed on the cycle ergometer were found to be reliable both prior to and after a training intervention (CV 1.3 - 3.3; ICC 0.87 - 0.98). Conclusion: Concurrent training in well trained cyclists does not appear to offer any performance benefits in terms of overall time trial or sprinting performance. However, the increase in strength with RT did not appear to be detrimental to overall performance. Furthermore, testing methods on a cycle ergometer appear to be reliable even after a training intervention.